Expansion of Human Megakaryocyte-Lineage Progeny via Aryl Hydrocarbon Receptor Antagonism with CH223191 - Dongchan Kim; Dong-Yeop Shin; Jun Liu; Na-rae Jeong; Youngil Koh; Junshik Hong; Xinxin Huang; Hal E. Broxmeyer; Sung-Soo Yoon (Stem Cell Reviews and Reports, 2022)

First report of natural infection of Jatropha integerrima by pepper mild mottle virus in Korea - Hae-Jun Kim; Hyo-Jeong Lee; Hyeong Woo Lee; Jin-Sung Hong; Rae-Dong Jeong (Journal of Plant Pathology, 2022)

Adaptive Formation Control of Multiple Underactuated Autonomous Underwater Vehicles - Ji-Hong Li; Hyungjoo Kang; Min-Gyu Kim; Mun-Jik Lee; Gun Rae Cho; Han-Sol Jin (Journal of Marine Science and Engineering, 2022)
In this paper, we present a 3D formation control scheme for a group of torpedo-type underactuated autonomous underwater vehicles (AUVs). These multiple AUVs combined with an unmanned surface vessel (USV) construct a sort of star-topology acoustic communication network where the USV is at the center point. Due to this kind of topological feature, this paper applies a virtual school concept. This is a geometric graph where each node is taken as a virtual leader for each specific AUV and assigned its own reference trajectory. For each individual vehicle, its formation strategy is simple: just follow the trajectory of its corresponding virtual leader so as for multiple AUVs to compose the given formation. As for the formation subject, this paper mainly focuses on the formation tracking problem rather than the formation producing. For the torpedo-type vehicle considered in this paper, there are only three control inputs (surge force, pitch, and yaw moments) available for its underwater 3D motion and therefore this is a typical underactuated system. For the following vehicle’s trajectory, a sort of potential field method is used for obstacle avoidance, and a neural network-based adaptive scheme is applied to on-line approximate the vehicle’s unknown nonlinear dynamics, and the uncertainty terms including modeling errors, measurement noises, and external disturbances are handled by the properly designed robust scheme. The proposed formation method can guarantee the uniform ultimate boundedness (UUB) of the closed-loop system. Numerical studies are also carried out to verify the effectiveness of the proposed scheme.